2021
DOI: 10.1002/jssc.202100234
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive determination of methionine by solvent‐based de‐emulsification dispersive liquid–liquid microextraction using bio‐stabilized silver nanoparticles

Abstract: In this study, a solvent‐based de‐emulsification dispersive liquid–liquid microextraction method coupled with surface plasmon resonance of silver nanoparticles was developed for determination of trace levels of methionine. The stable and dispersed silver nanoparticles were synthesized by applying ascorbic acid as reducer and Stenotrophomonas sp. bacterial suspension as bio‐stabilizer and then preconcentrated in organic phase according to a facile dispersive liquid–liquid microextraction procedure based on 1‐oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Studies have demonstrated that a deficiency of Met would result in several diseases, such as AIDS and Parkinson's disease [7]. Due to the clinical and physiological significance of Met [9], several methods have been established to detect Met, such as capillary electrophoresis [10,11], high-performance liquid chromatography [12,13], chemiluminescence [14], electrochemistry [15][16][17], fluorescence [18,19], and colorimetric methods [20,21]. However, these methods still have disadvantages such as high cost, a time-consuming process, and low sensitivity [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that a deficiency of Met would result in several diseases, such as AIDS and Parkinson's disease [7]. Due to the clinical and physiological significance of Met [9], several methods have been established to detect Met, such as capillary electrophoresis [10,11], high-performance liquid chromatography [12,13], chemiluminescence [14], electrochemistry [15][16][17], fluorescence [18,19], and colorimetric methods [20,21]. However, these methods still have disadvantages such as high cost, a time-consuming process, and low sensitivity [22][23][24].…”
Section: Introductionmentioning
confidence: 99%